Cooperative behaviour of autonomous robots - Pasquier, Michel B. (2008)
The purpose of this report was to investigate the application of various Soft Computing approaches and their integration with classical Artificial Intelligence technqiues to the realisationof a team of simple, cost-effecitve, hybrid autonomous robots based on a behavioural approach.